2018
DOI: 10.1007/s10461-018-2260-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Unhealthy Alcohol and Drug Use Among Men Who Have Sex with Men Prescribed HIV Pre-exposure Prophylaxis in Real-World Clinical Settings

Abstract: Pre-exposure prophylaxis (PrEP) is effective in preventing HIV acquisition among men who have sex with men (MSM). However, little is known about unhealthy substance use among MSM initiating PrEP in real-world settings. Unhealthy substance use is a risk factor for HIV acquisition and non-adherence to treatment, and may also impact PrEP use. MSM who were prescribed PrEP from 2015 to 2017 at clinics in Providence, Rhode Island and New Haven, Connecticut were recruited to participate in a prospective observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…The efficacy of PrEP depends on maintaining protective levels of adherence 5,6 . Substance use, particularly stimulant and alcohol use, is common among some MSM [7][8][9][10] , and is associated with HIV sexual transmission behaviors 10,11 and HIV acquisition 12 . Therefore, MSM who use substances could benefit from PrEP.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of PrEP depends on maintaining protective levels of adherence 5,6 . Substance use, particularly stimulant and alcohol use, is common among some MSM [7][8][9][10] , and is associated with HIV sexual transmission behaviors 10,11 and HIV acquisition 12 . Therefore, MSM who use substances could benefit from PrEP.…”
Section: Introductionmentioning
confidence: 99%
“…profilaktyka przedekspozycyjna: preparaty z emtrycytabiną i tenofowirem (np. Truvada™) [28][29][30]. Codzienne zażywanie przez mężczyzn homo-/biseksualnych emtrycytabiny-tenofowiru zmniejszało ryzyko zakażenia wirusem HIV o 99%, natomiast czterech tabletek tygodniowoo 96% [31].…”
Section: Skutki Zdrowotne I Społeczne Związane Z Chemseksemunclassified
“…A large body of evidence confirms the wide-ranging negative impacts of non-adherence [40,[43][44][45][46][47][48]. Other studies have demonstrated that RD use is associated with poor social, mental and financial health [33,34,38,40,42]. CM are also known as 'traditional' or 'alternative' medicines and include substances such as vitamins, minerals, herbal remedies, aromatic oils and homeopathic products [49].…”
Section: Introductionmentioning
confidence: 99%
“…As explained by Daskalopoulou et al, [28] the main mechanism of drug interaction occurs through the action of RD on the hepatic cytochrome p450 complex of enzymes, the nature and extent of which are yet to be fully understood. Even in the absence of potential RD-ART interactions, the negative consequences of RD use among PLHIV have been well documented [33][34][35][37][38][39][40][41][42]. For example, in their meta-analysis of contemporary research,…”
Section: Introductionmentioning
confidence: 99%